Corporate Governance and Equity Prices: The Effect of Board of Directors and Audit Committee Independence - Hamza, Taher; Mselmi, Nada (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2017)
This paper investigates the effect of board and audit committee independence on firm market performance. Using a sample of French listed firms, we find a negative and significant relation between board independence and equity returns. This suggests that appointing more independent directors fails in enhancing firm stock returns. Furthermore, we show that firms with independent audit committees exhibit higher equity returns. We analyze three portfolios sorted by the percentage of independent directors on boards and audit committees using Carhart’s model and find that the portfolio of firms with low board independence and high audit committee independence exhibits the highest abnormal returns.JEL Classification: G34, G11